Hypoxia Tolerance of 10 Euphausiid Species in Relation to Vertical Temperature and Oxygen Gradients - Tremblay, Nelly; Hünerlage, Kim; Werner, Thorsten (Frontiers in Physiology, 2020)
Oxygen Minimum Zones prevail in most of the world’s oceans and are particularly extensive in Eastern Boundary Upwelling Ecosystems such as the Humboldt and the Benguela upwelling systems. In these regions, euphausiids are an important trophic link between primary producers and higher trophic levels. The species are known as pronounced diel vertical migrators, thus facing different levels of oxygen and temperature within a 24 h cycle. Declining oxygen levels may lead to vertically constrained habitats in euphausiids, which consequently will affect several trophic levels in the food web of the respective ecosystem. By using the regulation index (RI), the present study aimed at investigating the hypoxia tolerances of different euphausiid species from Atlantic, Pacific as well as from Polar Regions. RI was calculated from 141 data sets and used to differentiate between respiration strategies using median and quartile (Q) values: low degree of oxyregulation (0.25< RI median <0.5); high degree of oxyregulation (0.5< RI median <1; Q1 >0.25 or Q3 >0.75); and metabolic suppression (RI median, Q1 and Q3 <0). RI values of the polar (Euphausia superba, Thysanoessa inermis) and sub-tropical (Euphausia hanseni, Nyctiphanes capensis, and Nematoscelis megalops) species indicate a high degree of oxyregulation, whereas almost perfect oxyconformity (RI median≈0; Q1 <0 and Q3>0) was identified for the neritic temperate species Thysanoessa spinifera and the tropical species Euphausia lamelligera. RI values of Euphausia distinguenda and the Humboldt species Euphausia mucronata qualified these as metabolic suppressors. RI showed a significant impact of temperature on the respiration strategy of E. hanseni from oxyregulation to metabolic suppression. The species’ estimated hypoxia tolerances and the degree of oxyconformity vs. oxyregulation were linked to diel vertical migration behaviour and the temperature experienced during migration. The results highlight that the euphausiid species investigated have evolved various strategies to deal with different levels of oxygen, ranging from species showing a high degree of oxyconformity to strong oxyregulation. Neritic species may be more affected by hypoxia, as these are often short-distance-migrators and only adapted to a narrow range of environmental conditions.